Left atrial late gadolinium enhancement is associated with atrial fibrillation as detected by continuous monitoring. (25th November 2020) - Bertelsen, L; Diederichsen, S.Z; Haugan, K.J; Brandes, A; Graff, C; Krieger, D; Kronborg, C; Kober, L; Peters, D.C; Olesen, M.S; Hojberg, S; Vejlstrup, N; et al.
Abstract: Background: Left atrial late gadolinium enhancement (LA LGE) measured with cardiac magnetic resonance (CMR) imaging is emerging as a marker of atrial fibrosis and has been associated with worse outcomes in AF ablation procedures. However, the prognostic value of LA LGE for incident AF remains unknown. Methods: CMR including measurement of left ventricular (LV) and LA volumes and function, as well as LV extracellular volume fraction and LA LGE, was acquired in 68 patients aged at least 70 years with risk factors for stroke. All included patients received and implantable loop recorder and were continuously monitored for previously unknown AF. Incident AF was adjudicated by senior cardiologists. Results: Patients were monitored for AF with implantable loop recorder during a median of 41 [36; 43] months. AF episodes lasting ≥6 minutes were detected in 32 patients (47%) and 16 patients (24%) experienced AF episodes lasting ≥5.5-hour. In Cox regression analyses adjusted for sex, age and comorbidities, we found that LA volumes and function and LA LGE were independently associated with incident AF. For LA LGE, the hazard ratio for time to AF episodes lasting ≥6 minutes and ≥5.5 hours were 1.40 (1.03, 1.89) per 10 cm 2 increase (p=0.03) and 1.63 (1.11, 2.40) per 10 cm 2 increase (p=0.01), respectively. LA LGE was significantly associated with high burden of AF. The addition of LA LGE to a multivariable risk prediction model for incident AF significantly increased the predictive value. Conclusions: Extent of LA fibrosis measured by LA LGE was significantly associated with incident AF detected by implantable loop recorder. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The Innovation Fund Denmark, The Research Foundation for the Capital Region of Denmark [no grant number]